Analysing Impact of Efficiency, Profitability, and Risk Management on Sustainable Performance of the Pakistani Banks - Muhammad sadiq, Malik; Sophee Sulong, Balia; Rossazana, Ab. Rahim; Naveed Iqbal, Chaudry (Allied Business Academies, 2022)
This conceptual paper aims to create a comprehensive framework for the Pakistani banks by analysing the impact of banks’ efficiency, profitability, and risk management capability on sustainable performance by incorporating most suitable determinants of banks specific internal and macroeconomic and external determinants. Internal determinants such as size of bank, capital ratio, loan intensity, credit risk, financial leverage, operating, return on asset (ROA), age of bank, Z-Score, bank ownership (foreign, domestic and government), and listing is studied and impact on efficiency, profitability, and risk management has been measured. Macroeconomic and external determinants such as Gross Domestic Product (GDP), inflation, interest rate, exchange rate, market capital, Global Financial Crisis, corruption control, and financial action task force (FATF) has been discussed and impact on efficiency, profitability, and risk management has been measured. During the process of research, the strands of reviewing literature show that renowned authors conducted independent studies on efficiency, profitability, and risk management and holistic studies analysing all these variables in one unison study are scarce. Whereas this paper has novelty that combines the impact of efficiency, profitability, and risk management capability on sustainable performance of banks and their corresponding banks’ specific internal and macroeconomic external determinants are researched. This conceptual paper has limitations as it is not empirically tested yet and this paper is based on literature review and suggests empirical testing of this framework through another study. This conceptual paper will contribute in assisting management of banking sector to measure sustainable performance of banks and will be helpful to the investors for making investment decisions for different banks.